2022
DOI: 10.1136/bjo-2022-321762
|View full text |Cite
|
Sign up to set email alerts
|

Use of ultrasound biomicroscopy to predict the outcome of anterior segment reconstruction in congenital fibrovascular pupillary membrane with secondary glaucoma

Abstract: AimsTo evaluate the efficacy and safety of anterior segment reconstruction (ASR) in congenital fibrovascular pupillary membrane-induced secondary glaucoma (CFPMSG) basing ultrasound biomicroscopy (UBM) classification.MethodsThis ambispective cohort study enrolled patients with CFPMSG who underwent ASR between January 2014 and September 2020. Comprehensive ophthalmic examinations and UBM were performed before surgery and postoperatively. The patients were classified into three types according to the UBM configu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 20 publications
0
3
0
Order By: Relevance
“…The diagnosis of FPM is based on close examination through a slit lamp. Ultrasound biomicroscopy (UBM) or anterior segment optical coherence tomography (AS-OCT) can be used for the diagnosis and differential diagnosis [17] [18]. In addition, these tests can reveal the origin of cells and tissues at the pathological level, but they cannot be applied in some clinical settings.…”
Section: Discussionmentioning
confidence: 99%
“…The diagnosis of FPM is based on close examination through a slit lamp. Ultrasound biomicroscopy (UBM) or anterior segment optical coherence tomography (AS-OCT) can be used for the diagnosis and differential diagnosis [17] [18]. In addition, these tests can reveal the origin of cells and tissues at the pathological level, but they cannot be applied in some clinical settings.…”
Section: Discussionmentioning
confidence: 99%
“…Zhu Y, et al reported 25 cases of congenital fibrovascular membrane with secondary glaucoma [ 10 ]. All cases had anterior segment reconstruction surgery, by performing peripheral iridotomy and blunt dissecting the membrane from the anterior lens capsule.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, they used UBM to classify the membrane severity. They found that class I had (72.7 %) success rate and additional surgery was needed in most of classes II and III [ 10 ].…”
Section: Discussionmentioning
confidence: 99%